Large-scale, national, family-based epidemiological study on Helicobacter pylori infection in China: the time to change practice for related disease prevention. Issue 5 (23rd January 2023) - Zhou, Xian-Zhu; Lyu, Nong-Hua; Zhu, Hui-Yun; Cai, Quan-Cai; Kong, Xiang-Yu; Xie, Pei; Zhou, Li-Ya; Ding, Song-Ze; Li, Zhao-Shen; Du, Yi-Qi
Abstract : Background and aims: Current practice on Helicobacter pylori infection mostly focuses on individual-based care in the community, but family-based H. pylori management has recently been suggested as a better strategy for infection control. However, the family-based H. pylori infection status, risk factors and transmission pattern remain to be elucidated. Methods: From September 2021 to December 2021, 10 735 families (31 098 individuals) were enrolled from 29 of 31 provinces in mainland China to examine family-based H. pylori infection, related factors and transmission pattern. All family members were required to answer questionnaires and test for H. pylori infection. Results: Among all participants, the average individual-based H. pylori infection rate was 40.66%, with 43.45% for adults and 20.55% for children and adolescents. Family-based infection rates ranged from 50.27% to 85.06% among the 29 provinces, with an average rate of 71.21%. In 28.87% (3099/10 735) of enrolled families, there were no infections; the remaining 71.13% (7636/10 735) of families had 1–7 infected members, and in 19.70% (1504/7636), all members were infected. Among 7961 enrolled couples, 33.21% had no infection, but in 22.99%, both were infected. Childhood infection was significantly associated with parental infection. Independent risk factors for household infection were infected family members (eg, five infected members: OR 2.72, 95% CI 1.86 to 4.00), living in highly infected areas (eg, northwest China: OR 1.83, 95% CI 1.57 to 2.13), and large families in a household (eg, family of three: OR 1.97, 95% CI 1.76 to 2.21). However, family members with higher education and income levels (OR 0.85, 95% CI 0.79 to 0.91), using serving spoons or chopsticks, more generations in a household (eg, three generations: OR 0.79, 95% CI 0.68 to 0.92), and who were younger (OR 0.57, 95% CI 0.46 to 0.70) had lower infection rates (p<0.05). Conclusion: Familial H. pylori infection rate is high in general household in China. Exposure to infected family members is likely the major source of its spread. These results provide supporting evidence for the strategic changes from H. pylori individual-based treatment to family-based management, and the notion has important clinical and public health implications for infection control and related disease prevention.